Chiral optofluidics: gigantic circularly polarized light enhancement of all-trans-poly(9,9-di-n-octylfluorene-2,7-vinylene) during mirror-symmetry-breaking aggregation by optically tuning fluidic media - Fujiki, Michiya; Abd Jalil, Jalilah; Suzuki, Nozomu; Taguchi, Makoto; Wei, Zhang; Mohamed Mehawed, Abdellatif; Nomura, Kotohiro (RSC Publishing, 2013)
Link to publisher's homepage at http://pubs.rsc.org/